Peran dan Keterlibatan Mahasiswa Keperawatan Anestesi dalam Mitigasi Bencana : A Scoping Review - Ririn Zuhairini; Sri Susilawati Kente; Syalwa Putri Fadilla Dinata; Assyifa Qolbi; Janjan Ningrum Pinasti (Jurnal Sains Farmasi Dan Kesehatan, 2025)
Disasters significantly impact health systems and require strong preparedness from healthcare providers, including nurse anesthesia students who possess key competencies in managing critically ill patients. This scoping review aims to map the roles, tasks, and preparedness of nurse anesthesia students in disaster mitigation. The study followed Arksey and O’Malley’s framework and PRISMA guidelines, with literature searched in PubMed and ScienceDirect for the years 2020–2025. From 661 identified articles, 11 met the inclusion criteria and were analyzed narratively. The synthesis revealed three main themes: strengthening pre-disaster capacity through education and simulation, students’ roles during disasters in triage and patient stabilization, and post-disaster learning through reflection and system evaluation. This review concludes that nurse anesthesia students have strategic potential in disaster mitigation, yet stronger integration of disaster content into curricula and more structured, continuous training are still needed.